Establishing a Networking Interinstitutional Law Enforcement - Villarreal-Sotelo, Karla (Universidad Autónoma de Tamaulipas, 2010)
Changes to the criminal justice system in our country do not concern only to those who administer justice, but also to all those areas of action which have an impact like in the academic side. The concern for scientific research on the impact of the new criminal constitutional reform, involves the study and localization of professional training of lawyers and criminologists. Therefore this is important to attend a series of criteria to establish an inner agency network known as: constitutional reform and the administration of criminal justice, organized by Academic Bodies registered with the Faculty Improvement Programme (Promep), involving the Universities of Tamaulipas, Nuevo León, Tlaxcala and The Autonomous University of Puebla. Also the time teachers who are working full-time free, and students of the Bachelor and Masters. The purpose of this research network focuses on the comprehensive study of the constitutional reform in criminal matters. Addressing the understanding of penal reform from its more complex aspects to emphasize strengths and weaknesses in the areas of education.